Hepatic connexin 32 associates with nonalcoholic fatty liver disease severity. Issue 7 (16th July 2018) - Luther, Jay; Gala, Manish K.; Borren, Nynke; Masia, Ricard; Goodman, Russell P.; Moeller, Ida Hatoum; DiGiacomo, Erik; Ehrlich, Alyssa; Warren, Andrew; Yarmush, Martin L.; Ananthakrishnan, Ashwin; Corey, Kathleen; et al.
Abstract : Emerging data highlight the critical role for the innate immune system in the progression of nonalcoholic fatty liver disease (NAFLD). Connexin 32 (Cx32), the primary liver gap junction protein, is capable of modulating hepatic innate immune responses and has been studied in dietary animal models of steatohepatitis. In this work, we sought to determine the association of hepatic Cx32 with the stages of human NAFLD in a histologically characterized cohort of 362 patients with NAFLD. We also studied the hepatic expression of the genes and proteins known to interact with Cx32 (known as the connexome) in patients with NAFLD. Last, we used three independent dietary mouse models of nonalcoholic steatohepatitis to investigate the role of Cx32 in the development of steatohepatitis and fibrosis. In a univariate analysis, we found that Cx32 hepatic expression associates with each component of the NAFLD activity score and fibrosis severity. Multivariate analysis revealed that Cx32 expression most closely associated with the NAFLD activity score and fibrosis compared to known risk factors for the disease. Furthermore, by analyzing the connexome, we identified novel genes related to Cx32 that associate with NAFLD progression. Finally, we demonstrated that Cx32 deficiency protects against liver injury, inflammation, and fibrosis in three murine models of nonalcoholic steatohepatitis by limiting initial diet‐induced hepatoxicity and subsequent increases in intestinal permeability. Conclusion: Hepatic expression of Cx32 strongly associates with steatohepatitis and fibrosis in patients with NAFLD. We also identify novel genes associated with NAFLD and suggest that Cx32 plays a role in promoting NAFLD development. ( Hepatology Communications 2018;2:786‐797)